The Relationship Between Learning Motivation and Self-Directed Learning Readiness Among Dental Students at YARSI University - Agus Ardinansyah; Sri Putri Damayanti; Nurhidayati Nosi (YARSI Dental Scientific Meeting - e Journal, 2025)
Background: Dental education today has adopted a student-centered learning (SCL) approach that emphasizes the importance of self-directed learning (SDL). Learning motivation is one of the main factors influencing students' readiness and effectiveness in SDL. Students with higher motivation tend to show greater initiative, better learning strategies, and stronger autonomy in managing their learning process. This study aimed to determine the relationship between learning motivation and self-directed learning among students of the Faculty of Dentistry at YARSI University. Methods: This was a descriptive analytic study with a cross-sectional design involving 282 students from both academic and clinical stages. The instruments used were the Strength of Motivation for Medical School (SMMS) and the Self-Directed Learning Readiness (SDLR) questionnaires, both of which had been validated and tested for reliability. Data were analyzed using univariate and bivariate methods, with Pearson correlation employed to assess the relationship between learning motivation and SDL. Results: The average SMMS score among students was 57.26, indicating a moderate level of learning motivation. The average SDLR score was 153.52, which falls into the high category for self-directed learning readiness. Pearson correlation analysis revealed a significant positive relationship between learning motivation and SDL, with a correlation coefficient of r = 0.286 and p = 0.000 (p < 0.05). Conclusion: There is a significant positive relationship between learning motivation and self-directed learning among dental students at YARSI University. Although the level of learning motivation was categorized as moderate, students demonstrated a high readiness for SDL. Enhancing learning motivation may further strengthen students' SDL abilities, thereby supporting more effective and independent learning processes.